Technology-based learning : maximising human performance and corporate success. - Marquardt, Michael J. (St. Lucie P. Boca RatonUS, 1999)
Describes the impact of technology on organizations and workers, and lists 14 ways in which it has transformed the workplace. Provides an overview of technologies for learning in the workplace, for example, electronic publishing, television and video. Looks at how technology is managing knowledge, and providing information and skills to the worker. Includes principles and practices necessary for utilisinsg technology in the global workplace. Lists internet sites for technology and learning in the workplace.